1×2 microstrip patch antennas array for mm-waves 5G application - Karima Benkhadda; Fatehi ALtalqi; Abdelhak Bendali; Abderrahim Haddad; Samia Zarrik; Sanae Habibi; Zahra Sahel; Mohamed Habibi; Abdelkader Hadjoudja (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
In this paper we present the design of an antenna array for 5G applications. The proposed prototype of the antenna array is design to function at both 24 GHz and 27 GHz frequencies, utilizing Rogers RT5880 with a permittivity equal to 2.2 and a loss tangent of 0.0009. The CST Studio Suite software is employed for simulating the suggested. The primary goals of this research encompass achieving a notable return loss, increased gain, minimized voltage standing wave ratio (VSWR), enhanced directivity, and an overall improvement in operational efficiency. The results of the simulation showcase encouraging performance metrics, including a return loss of -68.70 dB, a bandwidth larger 7.369 GHz (ranging from 22.191 GHz to 29.56 GHz), a gain of 10.52 dB. Furthermore, the microstrip patch antennas (MPA) array system showcases an impressive efficiency rating of 95.63%.